Etherification of Glycerol with Ethanol over Solid Acid Catalysts: Kinetic Study Using Cation Exchange Resin. Issue 2 (3rd April 2017) - Yadav, Vishnu P.; Maity, Sunil K.; Shee, Debaprasad
Abstract: The etherification of glycerol with ethanol is a novel process to utilise low-value by-product (glycerol) of the biodiesel industry to produce ethers of glycerol suitable for use as fuel additive or solvent. The etherification of glycerol with ethanol was investigated under the liquid phase in a high pressure batch reactor using two different types of commercial solid acid catalyst (zeolites and strongly acidic cation exchange resin (CER)). The CER showed superior catalytic activity over H-beta zeolite. The diethyl ether was observed as major product at high ethanol-to-glycerol mole ratio. The product selectivity diverted towards ethers of glycerol with decreasing ethanol-to-glycerol mole ratio. Among ethers of glycerol, glycerol monoethyl ether was the major product of the reaction. The reaction mechanism for etherification of glycerol with ethanol was delineated based on experimental observations. The reaction rate increased with increasing catalyst loading and temperature without affecting selectivity to the products significantly. The apparent activation energy of glycerol and ethanol was 25.1 and 26.6 kcal/mol, respectively. An empirical kinetic model was developed to correlate experimental data at different temperatures. The conversion of the reactants calculated from the kinetic model matched reasonably with experimental data.